NSE Stock Prediction Using ANN Models - Muskaan, Pradeepta Kumar Sarangi (International Journal of Control and Automation, 2020)
Analyzing the stock trend and forecasting the future direction is a challenging task. Researchers apply various methods to predict the stock trend but still there is no method that can guarantee the stock movement. However, a nearly approach could be achieved in case of short-term movement. In this paper we have analyzed the short-term stock prediction using the forecasting through Artificial Neural Network (ANN). The experiments have been done the stock prices of ICICI Bank listed in NSE, India.